Manufacturing not sensitive Okougl Omaid poly Funnell alcohol suitable for technical (Baghdad Science Journal, 2005)
A sensitive film was manufactured Holokravaa using plastic materials the a Akougl substantive Amaid with poly alcohol Funnell addition to sensitive material Daakromat ammonium were obtained registry Qakma to diffraction efficiency of 83%